2002
DOI: 10.1002/pros.10077
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid stimulates proliferation of cultured smooth muscle cells from human BPH tissue: Sildenafil and papaverin generate inhibition

Abstract: The major conclusion of this investigation is that the endogenous serum component LPA, is able to promote human BPH SMC growth. In addition, our study indicates that cyclic nucleotides can inhibit this effect. Future clinical studies will be needed to determine if different specific phosphodiesterase inhibitors per se or in combination could represent a new therapeutic possibility for the treatment of BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 36 publications
4
18
0
1
Order By: Relevance
“…Examination of human tissues revealed similar findings (16,47). In addition to modulating SM tone by cGMP degradation, PDE5 also regulates cell proliferation (2,74). Zenzmaier et al (74) have reported that tadalafil reduces proliferation of primary prostate stromal cells and to a lesser extent primary prostate basal epithelial cells in a dose-dependent manner.…”
supporting
confidence: 52%
“…Examination of human tissues revealed similar findings (16,47). In addition to modulating SM tone by cGMP degradation, PDE5 also regulates cell proliferation (2,74). Zenzmaier et al (74) have reported that tadalafil reduces proliferation of primary prostate stromal cells and to a lesser extent primary prostate basal epithelial cells in a dose-dependent manner.…”
supporting
confidence: 52%
“…Recent reports suggests that cGMP accumulation could have an antiproliferative effect on smooth muscle cells of the prostate [20]. A previous report showed that Zaprinast can reduce proliferation in prostatic stromal cells and in cultured smooth muscle cells from patients with BPH [21,22]. Antiproliferative effect of all commercially available PDE5 inhibitors on BPH smooth muscle cells has been shown [9,22].…”
Section: Discussionmentioning
confidence: 95%
“…Following accumulation of cGMP, hyperpolarization, rapid drop in intra--cytoplasmic calcium and finally relaxation of smooth muscle will happen (22,23). In vitro study showed that sildenafil inhibits the growth of prostatic smooth muscle cells (24). Inhibition of PDE-5 in the prostate may have a positive impact on dynamic component of LUTS by decreasing sympathetic tone (7).…”
Section: Discussionmentioning
confidence: 99%